A New Method towards Achieving FES-Induced Movement - Ahmed, Mohammed (International Journal of Integrated Engineering, 2018)
Literature has revealed that applications of Functional Electrical Stimulation (FES) for restoration of movements have been yielding promising results in people with impaired neural system. Records indicate rise in subjects with such disabilities without corresponding increase in orthosis devices using FES. The scarce available ones have high cost which could be due strict clinical requirement imposed on such equipment. In order to alleviate the aforementioned challenges an approach was proposing procedure to the system. It suggested improvements for three basic components: plant modelling, remoudelling the fatigue, spasm and tremor disturbances from the works of Lynch et al., and finally a combined Sliding Mode and Wavelets techniques availing a new control approach for the FES to facilitate safe sit-to-stand movement. There some basic similarities in the sit-to-stand and knee swinging such as; pivot point and muscles stimulated during the processes. The knee joint model proposed by Ferrarin and Pedotti and the disturbances models (fatigue, tremor and spasm) developed by Lynch et al. would be utilized as stated earlier. The procedure was to be conducted phases: plant modeling, disturbances modelling and control system design. Expectations include enhancing subject condition, interactions with others and environment, delivery of health care, self-reliance and reducing health maintenance costs.